Determinants of spread bank in Chile - Gutiérrez Urzúa, Mauricio (2014)
The determinants of spread are internal variables of each bank, market variables and macroeconomic variables. The behavior of each of these variables on spreads, can determine the efficiency of the financial system. To establish the relationship-specific data are used a number of banks in the market and perform regressions, according to the characteristics of these To determine the regressions used the fixed effects model and random effects model and generalized least square (GLS). The paper shows that Chile has an inefficient banking market, due to its monopolistic tendencies. While this inefficiency does not create competitive disadvantages worldwide, generates an extra charge for local customers